Bell's Palsy: A Need for Paradigm Shift? - Jain, Shraddha; Kumar, Sunil (Annals of Otology and Neurotology, 2018)
Introduction Bell's palsy (BP) is considered to be idiopathic facial palsy. Some schools of thought believe it to be a part of polyneuropathy, whereas other scientists have other plausible explanations for the condition and all these were reviewed.Methods The literature on BP was retrieved using the Cochrane Database of Systematic Reviews, PubMed, and Google Scholar. Keywords and phrases used during the search included “Bell's palsy,” “polyneuropathy,” “anatomical factors,” and “autoimmunity.”Results There are only few studies that have tried to find out the association of BP with peripheral nerve conduction abnormalities. In most studies conducted, positive correlation was found. There are many theories of its etiology, with the reactivation of herpes simplex virus isoform 1 and/or herpes zoster virus (HZV) from the geniculate ganglia being the most strongly suspected cause.Conclusion In the future, large studies will be required to determine the association between peripheral neuropathy and BP and elucidate the real etiology in every case. There will also be a need to determine whether BP should still be considered idiopathic and isolated.
Keywords: Bell's palsy; peripheral neuropathy; idiopathic facial paralysis; herpes simplex virus; autoimmunity; genetic